Beyond smell: rethinking the figurative force of olfactory language - Lang, Jun; Shi, Heidi Hui; Jing-Schmidt, Zhuo (De Gruyter, 2025)
This study examines the usage, semantics, and affective valence of olfactory metaphors in English, addressing a gap in sensory language and metaphor research. We analyze eight basic smell lexemes (smell, aroma, scent, odor, stench, stink, reek, fragrance) in the iWeb corpus, tracing their abstract noun collocates through frequency counts, WordNet hypernym paths, intersection analysis, and affective valence ratings. Our results reveal that English olfactory metaphors are highly productive, mapping smell perception onto a broad array of abstract experiences, especially socioemotional and moral domains. The eight patterns exhibit pronounced affective polarization: while some (e.g., fragrance, aroma) skew positive, most (e.g., stink, stench, reek, odor) skew negative, reflecting both olfactory hedonics and a cognitive negativity bias. These findings deepen our understanding of how sensory language structures abstract thought and affirm the rich figurative potential of smell in English, with implications for theories of sensory language, conceptual metaphor, and embodied cognition.
Keywords: smell; olfactory metaphor; sensory language; emotion; morality